Treinamento de força ameniza alterações comportamentais e neuroquímicas induzidas por um modelo de transtorno bipolar em ratos - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Bipolar disorder (BD) is a central nervous system condition typified by mood fluctuations oscillating between depressive, manic, and/or hypomanic episodes. This study aimed to assess the potential of strength training as a protective agent against BD. Male Wistar rats underwent a strength training protocol and, following training, received a single ouabain dose before behavioral testing. Post-euthanasia, hippocampal samples were collected for biochemical analyses of pathways associated with myogenesis and neurogenesis. Results showed that strength training protected against ouabain-induced behavioral deficits, including increased locomotion, risk-taking, aggression, and memory impairment. Training also preserved activation of the BDNF/ERK/CREB pathway, linked to neurogenesis, and increased activation of the AKT/mTOR myogenic pathway. These findings indicate strength training's positive effect in attenuating or preventing BD-related deficits, suggesting its therapeutic potential as an adjuvant treatment for BD patients.
Strength training attenuates behavioral and neurochemical changes in ouabain-induced bipolar disorder in rats
Keywords: Resistance exercise; Myogenic pathway; Exercício de resistência; Via miogênica; Mania; Depression; Depressão; Agressividade; Aggressiveness; Anxiety-like behavior; CNPQ::CIENCIAS BIOLOGICAS